Analisis Efek Doppler dan Implementasinya pada Sistem Radar dan Telekomunikasi: Sebuah Kajian Literatur - Mendrofa, Doniman; Harefa, Fajar (CV. SINAR HOWUHOWU, 2025)
The Doppler Effect is a physical phenomenon caused by the relative motion between a wave source and an observer, resulting in a shift in the received wave frequency. This study aims to analyze the Doppler Effect and its implementation in radar and telecommunication systems through a literature review. The findings reveal that the Doppler Effect is a fundamental principle in radar technology, enabling accurate detection of speed, distance, and direction of objects. In telecommunications, however, the Doppler Effect poses challenges, such as frequency shifts that may affect signal quality, particularly in mobile networks, satellite communication, and autonomous vehicles. Various compensation techniques, including adaptive coding and frequency tracking, have been developed to address these issues. The study also highlights technological innovations based on the Doppler Effect, including weather radar, Doppler lidar, and 5G communication networks, showcasing their significant potential for future applications.